PENGARUH KEPEMILIKAN ULTIMAT TERHADAP NILAI PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Khomsiyah khomsiyah; Lisa Lorentia (Jurnal Magister Akuntansi Trisakti, 2020)
The objective of this research is to analyze the influence of ultimate ownership on firm’s value of companies listed in indonesia stock exchange. Ultimate ownership is proxied by cash flows right and cash flows right leverage of the ultimate owner, while firm value is measured using Tobin’s Q. Sample of this research are 117 companies which are listed in Indonesia Stock Exchange with the study period of 2015 which are chosen by using purprosive sampling method. Multiple regression and hypotheses testing are used as the data analysis method in this research. The result of this research shows that cash flows right does not have influence on firm’s value, while cash flows right leverage has positive influence on firm’s value.